2006
DOI: 10.1890/05-0090
|View full text |Cite
|
Sign up to set email alerts
|

Biotic Habitat Complexity Controls Species Diversity and Nutrient Effects on Net Biomass Production

Abstract: Canopy-forming plants and algae commonly contribute to spatial variation in habitat complexity for associated organisms and thereby create a biotic patchiness of communities. In this study, we tested for interaction effects between biotic habitat complexity and resource availability on net biomass production and species diversity of understory macroalgae by factorial field manipulations of light, nutrients, and algal canopy cover in a subtidal rocky-shore community. Presence of algal canopy cover and/or artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 19 publications
3
88
0
6
Order By: Relevance
“…Accordingly, earlier experiments at the study site demonstrated that the production of algal biomass is controlled by light availability in a quadratic relation (Pearson moment correlation of bottom light availability and the square root of the macroalgal biomass accumulated over summer on propagule-seeded bricks in 2004 and 2005: n = 42, t, p, R 2 = 0.58; Fig. 1) and that nutrients increase biomass production only at high light (Eriksson et al 2006(Eriksson et al , 2007. Thus, the square root of biomass development of already established macroalgal propagules should therefore provide a good relative measure of resource availability and primary production at our field site (Eriksson et al 2006), while the abundance of recruits should represent the fraction of the algal community sensitive to consumer control.…”
Section: Study Sitementioning
confidence: 76%
See 4 more Smart Citations
“…Accordingly, earlier experiments at the study site demonstrated that the production of algal biomass is controlled by light availability in a quadratic relation (Pearson moment correlation of bottom light availability and the square root of the macroalgal biomass accumulated over summer on propagule-seeded bricks in 2004 and 2005: n = 42, t, p, R 2 = 0.58; Fig. 1) and that nutrients increase biomass production only at high light (Eriksson et al 2006(Eriksson et al , 2007. Thus, the square root of biomass development of already established macroalgal propagules should therefore provide a good relative measure of resource availability and primary production at our field site (Eriksson et al 2006), while the abundance of recruits should represent the fraction of the algal community sensitive to consumer control.…”
Section: Study Sitementioning
confidence: 76%
“…The Schlei Fjord is characterized by insignificant tides, and in the summer, the salinity ranges between 12 and 18 PSU (practical salinity units), nutrient concentrations fluctuate highly, and water temperatures range between 16 and 25°C (Worm and Lotze 2006). The sandy benthos scattered with rocks support a submerged macroalgal community dominated by the canopy-forming macroalgae Fucus vesiculosus (hereafter Fucus), which covers approximately 80% of the stone surface along with several crust-forming species and a number of fastgrowing green ephemerals (Eriksson et al 2006). The grazer community consists of small peracarid crustacean mesograzers (isopods and amphipods) and 1-to 2-cmsized snails (mainly periwinkles, Littorina littorea, and L. saxatilis).…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations